Dual Clinical Collaborator: A Pragmatic Role of nurses from developing countries - Ohri, Uma; Nirisha P, Lakshmi; Poreddi, Vijayalakshmi; Manjunatha, Narayana; Kumar C, Naveen; BadaMath, Suresh (Investigación y Educación en Enfermería, 2024)
Collaboration is crucial in Professional nursing practice. Nurses act as a liaison between physicians and patients and their family members. Thus, it is vital to define the collaborative role of nurses in developing countries. The authors discuss pragmatic nurses’ role by adopting the Dual Clinical Collaborator model to ensure offering the quality of care to their clients. Nursing is a healthcare profession that focuses on the care of individuals and their families to help them recover from illness and maintain optimal health and quality of life. Health Care Professionals (HCPs) work together to provide quality health care and accomplish common goals. As healthcare delivery is becoming more complex, collaboration among healthcare workers and the patient can be a path to improve the quality of healthcare services.